Self-regulation As A Method Of Achieving psychological Well-being - Kryvokon, Natalia; Pavlenko, Anna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article is devoted to the problem of self-regulation and psychological well-being. Self-regulation is understood as a conscious process of human mental activity that constructs, maintains and manages its arbitrary activity aimed at achieving the goals. Psychological well-being is treated as a set of personal resources, which provide a harmonious relationship as a system «subject-environment». The relevance of the phenomenon of self-regulation research is examined, the examples of foreign and domestic researches are given, the key scientifi positions on the issue of self-regulation and psychological well-being are presented. The need for further theoretical and experimental studies of the phenomenon of self-regulation is stressed.